Leaders' decision making and neuroscience : what are you thinking? - Wang, Yinying (Emerald Publishing Limited, 2024)
What, exactly, is leadership? Leadership is about motivating a group of people to achieve a common goal. Ever since the dawn of the field of leadership, people have craved an understanding of invisible mental processes that underlie visible behavior. Why do people behave the way they do? Where does behavior come from? Consider your brain is a decision-making organ. Without the brain, you are unable to make decisions. You will learn how power, emotions, attention, memory, personality, and gut feeling influence your decisions. You will learn neural constraints imposed on your decision making and how to address them. In addition to learning how to make high-quality individual decisions, you will learn how to ensure a group makes high-quality decisions collectively. How does a collective mind emerge from multiple minds when making collective decisions? What should leaders do to facilitate a group decision-making process that generates collective wisdom, instead of the madness of crowds? If you are a leader, or aspire to be a leader, who strives to make high-quality decisions, this is the book for you. Leaders' Decision Making and Neuroscience will take you on a journey of how a decision is made in your brain from a perspective of neuroscience and provides incredible insight into the nature of how the brain and nervous systems work in relation to decision making.
Includes index.
Keywords: Leadership.; Management -- Decision making.; Business & Economics -- Leadership.; Management: leadership & motivation.; elektronické knihy; electronic books